2020
DOI: 10.5897/jmpr2020.6962
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey of medicinal plants commonly used in snakebites in North Western Nigeria

Abstract: The incidence of snake bite in rural West Africa is reportedly high with an 11-17% mortality rate. Nigeria has one third of the cases for snake bite cases in this region.Thus, most tribes in Northwestern part of Nigeria depend on medicinal plants for snakebites. However, it appears that a gap exists on documentation of these plants especially tropical flora used in the management of snake bite. This led to increase depletion of medicinal plant resources and knowledge of their traditional use. Consequently, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Aromatic and medicinal plants have played a crucial role in the treatment and prevention of a wide range of diseases for thousands of years [ 1 ]. The therapeutic uses of herbs are based on plant chemistry [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic and medicinal plants have played a crucial role in the treatment and prevention of a wide range of diseases for thousands of years [ 1 ]. The therapeutic uses of herbs are based on plant chemistry [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in southern Algeria, the investigation realized by Telli et al (2016) showed that among 289 diabetic patients interviewed, 60.90% use antidiabetic plants. However, only 28.30% use medicinal plants among 470 people with diabetes interviewed in southwestern and northwestern Algeria (Rachid et al, 2012). This difference may be related to the degree of availability of plants (vegetal cover) and the degree of attachment to traditional medicine by societies.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in accordance with those revealed by other Algerian scientists. The results of Rachid et al (2012) showed that more than 36% of type 2 diabetic patients used medicinal plants but only 17.16% in type 1 diabetes cases. Similarly, Allali et al (2008) have noticed during their ethnobotanical study that more than 66% of type 2 diabetic patients used plants against 33.8% only in the type 1 diabetic population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, global advocacy for increased research for documenting traditional medicinal knowledge and conservation of medicinal plants has also increased significantly in recent times ([ 2 , 11 , 19 , 21 ]). Though the study of medicinal plants has been explored from diverse perspectives, one area receiving increased research interest in recent times is the study of medicinal plants using ethnobotanical and ethnopharmacological approaches ([ [10] , [11] , [12] , 17 , 21 , 22 ]). These authors have argued that such knowledge is critical for developing medicinal plants and discovering new drugs ([ 11 , 12 ]).…”
Section: Introductionmentioning
confidence: 99%